Benefits of code-switching in language learning classroom at University of Education Lahore - Shafi, Sidra; Kazmi, Syeda Hiraa; Asif, Rehman (International research journal of management, IT and social sciences, 2020)
Code-switching refers to the use of more than one language in a sentence or discourse. It is a natural commix that happens in utterances in bilingual and multilingual speakers reasoning one or more communal languages. Code-switching (CS) denotes an alteration that is recorded between more than one variation in language following in the context of a single conversation. In sociolinguistics, code-switching is considered not merely one element of social life but encircles the social strata of speakers’ social settings, linguistic variation and social variables. It is a linguistic strategy of bilingual or multilingual speakers. It is referred to as a “conversational scheme which is employed to constitute, cross or abolish group boundaries, to create, evoke or change interactive relation with their rights and commitments”. (Gal, 1988). In multilingual contexts like Pakistan, code-switching is a common phenomenon. It appears as a conscious choice of language teachers to promote second language (L2) learning and improve second language comprehension among L2 learners. This article highlights the benefits of code-switching in the course of learning, explores some of the aspects of code-switching and its effectiveness in increasing L2 comprehension among the students at UE.